The connection between autophagy and ferroptosis in AKI: recent advances regarding selective autophagy - Chunyu Pan; Hairui Zhao; Xiaojing Cai; Manyi Wu; Bowen Qin; Junhua Li (Renal Failure, 2024)
Acute kidney injury (AKI) is a significant issue in public health, displaying a high occurrence rate and mortality rate. Ferroptosis, a form of programmed cell death (PCD), is characterized by iron accumulation and intensified lipid peroxidation. Recent studies have demonstrated the pivotal significance of ferroptosis in AKI caused by diverse stimuli, including ischemia-reperfusion injury (IRI), sepsis and toxins. Autophagy, a multistep process that targets damaged organelles and macromolecules for degradation and recycling, also plays an essential role in AKI. Previous research has demonstrated that autophagy deletion in proximal tubules could aggravate tubular injury and renal function loss, indicating the protective function of autophagy in AKI. Consequently, finding ways to stimulate autophagy has become a crucial therapeutic strategy. The recent discovery of the role of selective autophagy in influencing ferroptosis has identified new therapeutic targets for AKI and has highlighted the importance of understanding the cross-talk between autophagy and ferroptosis. This study aims to provide an overview of the signaling pathways involved in ferroptosis and autophagy, focusing on the mechanisms and functions of selective autophagy and autophagy-dependent ferroptosis. We hope to establish a foundation for future investigations into the interaction between autophagy and ferroptosis in AKI as well as other diseases.